Comparison of the Effect of Breast Sucking with Being in the Mothers Hug on Pain Relieving during Immunization Injection - SH Shah Ali (Babol University of Medical Sciences, 2009)
BACKGROUND AND OBJECTIVE: Since neonates have higher pain sensitivity, pain management has become a crucial part of neonatal care and cure. The objective of this study was to compare the effect of breast-sucking with being in the mothers hug on pain relieving during immunization injection.METHODS: This controlled trial study was performed on 76 healthy term infants with 2-4 months years old. They were divided into two groups. By randomized collection one group were breast-fed, 2 minutes before, during, and 15 seconds after the injection, and second were in their mothers hug 2 minutes before, during, and 15 seconds after the injection. Modified Behavioral Pain Scale (MBPS) assessed objective changes in appearance of neonates (facial expression, cry and movements) during 5 second before immunization to 15 second after it. The scores for each behavior were calculated and compared in two groups.FINDINGS: There were significant differences in behavioral pain scores of breast-fed group (4.6±1.8) and mothers hug (6.7±1.2) include facial expression (p=0.032), cry (p=0.0001) and movements (p=0.0001) and there is no statistically significant difference found between the 2 groups for age, sex and the time of feeding prior to vaccination.CONCLUSION: Breast-feeding may have an analgesic effect during immunization injections in healthy neonates.